2006
DOI: 10.1111/j.1365-2486.2006.01250.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid climate change‐related growth decline at the southern range edge of Fagus sylvatica

Abstract: Studies on Fagus sylvatica show that growth in populations toward the southern limit of this species' distribution is limited strongly by drought. Warming temperatures in the Mediterranean region are expected to exacerbate drought where they are not accompanied by increases in precipitation. We studied levels of annual growth in mature F. sylvatica trees over the last half-century in the Montseny Mountains in Catalonia (northeast Spain). Our results show significantly lower growth of mature trees at the lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
422
5
21

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 594 publications
(492 citation statements)
references
References 42 publications
26
422
5
21
Order By: Relevance
“…The processes and rates of carbon sequestration are expected to vary as a consequence of the onset and duration of such forest dieback [21,24,78], with the effect of reduced uptake potentially being magnified by increases in carbon released from tree decomposition [31]. Carbon sequestration can be reduced even in the absence of mass mortality events via tree growth decline and elevated mortality rates, as reported recently at the southernmost range edge of beech distribution in Europe [65,66], and in temperate trees across the western USA [31]. Furthermore, such alterations to carbon economy are occurring despite the predicted enhancement of water-use efficiency by increasing CO 2 and its expected fertilization effect (higher atmospheric CO 2 concentrations leading to higher plant productivity) [79].…”
Section: Carbon Sequestrationmentioning
confidence: 91%
See 2 more Smart Citations
“…The processes and rates of carbon sequestration are expected to vary as a consequence of the onset and duration of such forest dieback [21,24,78], with the effect of reduced uptake potentially being magnified by increases in carbon released from tree decomposition [31]. Carbon sequestration can be reduced even in the absence of mass mortality events via tree growth decline and elevated mortality rates, as reported recently at the southernmost range edge of beech distribution in Europe [65,66], and in temperate trees across the western USA [31]. Furthermore, such alterations to carbon economy are occurring despite the predicted enhancement of water-use efficiency by increasing CO 2 and its expected fertilization effect (higher atmospheric CO 2 concentrations leading to higher plant productivity) [79].…”
Section: Carbon Sequestrationmentioning
confidence: 91%
“…Regeneration thus becomes sparse, whereas a more resilient old generation persists [64]. These impacts are evident in the European beech, where trailing range-edge populations are threatened by increasingly rare recruitment and declining growth of remaining adult trees as temperatures increase [12,51,65,66].…”
Section: Ecological Explanationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bontemps et al, 2010;Delpierre et al, 2009;Pan et al, 2013;McMahon et al, 2010) as well as negative ones have been found (e.g. Barber et al, 2000;Jump et al, 2006;Charru et al, 2010). However, it remains unclear why forests react differently to temperature change.…”
Section: Introductionmentioning
confidence: 99%
“…As comprehensively explained by Brumme and Khanna (2009), its increased cultivation in central Europe is heavily advocated to preserve and enhance biodiversity in a changing climate and to provide long-term sustainability of forests and the productivity of forest stands. In this situation, some concern has been expressed about the relatively small knowledge base about the response of European beech to drought conditions (Jump et al 2006;Geßler et al 2007;Friedrichs et al 2009). Our model evaluation takes advantage of extensive data from two areas in south-west Germany that have repeatedly been investigated for forestry and ecophysiological purposes (e.g.…”
Section: Introductionmentioning
confidence: 99%